Antifungal activity of essential oil extracted from Melaleuca alternifolia against pathogenic fungi on mangoes (Mangifera Indica L.) for mango postharvest application - Gunny, Ahmad Anas Nagoor; Seminai, Jenny Janam Anak; Che Mat, Mohd Hishamuddin; Ahmad, Abdul Aziz; Yusof, Rizana (2021)
Abstract. An infection from pathogenic fungi is one of the main reasons causing the losses of mangoes during postharvesl. An essential oil from Melaleuca alternifolia is being introduced as natural fungicide in controlling postharvest disease of mangoes. The extraction of essential oil from Melaleuca alternifolia was performed using Solvent Free Microwave Assisted Extraction with yield of 0.5% The inhibitory effect of essential oil extracted from . Melaleuca alternifolia against isolated fungi from mango was investigated through in-vitro and in-vivo analysis. Distilled water was used as negative control while chemical fungicide (Globus 5.5) as positive control in the analysis. The mycelial growth inhibition of extracted essential oil for poisoned food test and disc diffusion test showed 62.50 % ±0.49 and 59.70 %± 0.30 respectively for in-vivo experiment which had artificially wounded and unwounded mangoes. The result also demonstrated that the essential oil applied on the wounded mangoes could decrease the disease incidence from l00% to 61.33% for up to 10 days kept at room temperature compared to that of the control. Hence. the essential oil of Melaleuca alternifolia can act as green fungicide and is also a promising alternative to the synthetic chemical fungicide for controlling postharvest disease on mangoes.